FACTORS RELATED TO THE INCIDENCE OF ABORTION AT RSUD dr. SLAMET, GARUT REGENCY, WEST JAVA - Ika Zakiah; Khodijah, Upus Piatun (Program Studi D III Kebidanan Akademi Kesehatan Sapta Bakti Bengkulu, 2023)
Abortion is the threat or discharge of the result of conception in pregnancy less than 20 weeks or fetal weight less than 500 grams. . About 5 percent of couples trying to conceive will have 2 consecutive miscarriages (habitual abortion), and about 1 percent of couples have 3 or more consecutive miscarriages. The purpose of the Research is known Factors related to abortion At RSUD dr. SLAMET Garut in 2021.The research method taken was case control, with a population of all first and second trimester pregnant women with a total sampling technique of 70 respondents. The results of the study obtained were a relationship between maternal age (p value 0.009), parity (p value 0.031), work (p value 0.014), and education (p value 0.000), with the incidence of abortion at RSUD dr. SLAMET Garut period June 2021. Conclusion: There is a significant relationship between age, parity, occupation, and education with the incidence of abortion in RSUD dr. SLAMET Garut Period June 2016 with for education. Suggestion: This research is expected to be used as knowledge for the general public so that it can be used as knowledge about the signs of abortion